Potencial prognóstico e terapêutico do receptor de quimiocinas CCR5 na carcinogênese - Andrade, João Lucas Corrêa De (2023)
The aim of this study was to evaluate the potential effect of CCR5 chemokine receptor inhibition on cancer development and progression. This dissertation was prepared in the form of two articles, the first a systematic review and the second an in vitro study. In the systematic review, in addition to evaluating the approaches used to inhibit CCR5, as well as their effects on the development and progression of cancer, the quality of preclinical studies in animals was also evaluated. The systematic review was performed according to PRISMA guidelines using a structured search in PubMed/MEDLINE, Scopus, Web of Science and Embase databases, retrieving and analyzing 21 original studies. For the analysis of the risk of bias and the methodological quality of the studies, the tool developed by SYRCLE (Systematic Review Center for Laboratory Animal Experimentation) was used. Promising results were identified after CCR5 inhibition in different types of cancer, which were mainly associated with a reduction in tumor size. However, the mechanisms underlying this reduction were quite variable between studies. In addition, most of the experiments used Maraviroc as a CCR5 inhibitor. When analyzing the methodological quality of the studies, potential risks of bias were identified in the different domains evaluated. Thus, this review provides objective support to delimit future studies with greater methodological rigor, providing unequivocal evidence on the impact of CCR5 inhibition on cancer development and progression. In view of the relevance of the results found and the scarcity of studies on CCR5 inhibition in the context of oral carcinogenesis, an in vitro study was carried out. In the in vitro study, the expression of CCR5 in different cell lines (CAL27, SCC4, SCC9, SCC15, SCC25 and HSC3) of oral squamous cell carcinoma (OSCEC) and the effects of its inhibition by treatment with Maraviroc (MVC) were evaluated. The highest expression of CCR5 was detected in cell lines SCC15 and SCC25 which, therefore, were selected for functional assays. The results of this study demonstrated that treatment with MVC resulted in a significant decrease in cell proliferation and migration of SCC15 and SCC25 cells, depending on the concentration and time of exposure to the treatment. These results suggest that MVC treatment plays an important role in the tumor biology of CCEOs and may represent a new strategy for the treatment of oral cancer. However, further studies are needed to better understand the mechanisms associated with the treatment of CCEO with MVC.